Concise Review: The Use of Stem Cells for Understanding and Treating Huntington's Disease. (5th December 2017) - Connor, Bronwen
Abstract : Two decades ago, researchers identified that a CAG expansion mutation in the huntingtin ( HTT ) gene was involved in the pathogenesis of Huntington's disease (HD). However, since the identification of the HTT gene, there has been no advance in the development of therapeutic strategies to prevent or reduce the progression of HD. With the recent advances in stem cell biology and human cell reprogramming technologies, several novel and exciting pathways have emerged allowing researchers to enhance their understanding of the pathogenesis of HD, to identify and screen potential drug targets, and to explore alternative donor cell sources for cell replacement therapy. This review will discuss the role of compensatory neurogenesis in the HD brain, the use of stem cell-based therapies for HD to replace or prevent cell loss, and the recent advance of cell reprogramming to model and/or treat HD. These new technologies, coupled with advances in genome editing herald a promising new era for HD research with the potential to identify a therapeutic strategy to alleviate this debilitating disorder. Abstract : Stem cells play an important role to enhance our understanding and treatment of Huntington's disease (HD). This review discusses the role of (a) compensatory neurogenesis in the HD brain, (b) the use of stem cell-based therapies for HD to replace or prevent cell loss, and (c, d) advances in cell reprogramming to model and/or treat HD.